UTILIZATION OF COURSE REFRESHER IN ASSESSING AND FACILITATING TEACHER-LEARNING (CRAFT) FOR PROFESSIONAL FACULTY DEVELOPMENT - Mallillin, Leovigildo Lito D. (2023)
The study aims to identify the utilization of course refresher in assessing and facilitating teacher-learning (CRAFT) for professional faculty development and analyses what makes utilization of course refresher in assessing and facilitating teacher-learning (CRAFT) becomes professional faculty development such as role, understanding, expectation, development of trust and respect, organizational and institutional development culture, and perspective faculty success. Mixed method is utilized in the study through Focus Group Discussion (FGD). It is a combination of quantitative and qualitative research. Likewise, purposive sampling is employed in the study. It is appropriate in collecting the sample population of the target population. It is subjective sampling, selective, and judgmental. The study comprised one hundred seventy-five (175) respondents only. Results show that utilization of course refresher in assessing and facilitating teacher-learning (CRAFT) for professional faculty development promote collaboration and decision making on dynamic converging issues requiring leadership setting, attention, and teamwork goal orientation in the school culture environment, roles, understanding, and expectation shows to build professional development of faculty benefit and ability for personal goals and potentials, development of trust and respect show to have socialization in education provided by the school organization behaviour process of individual employee faculty, organizational and institutional development culture show to promote and engage healthy behaviour in organizational and institutional development culture among faculty and staff to display high professional standards, and perspective faculty success shows to be responsible for academic output and achievement instruction guide task assignment of faculty success and responsibility to improve academic performance and support student success and experience in teaching and learning. Findings show that there is a significant relationship on the course refresher in assessing and facilitating teacher-learning (CRAFT) for professional faculty development as observed by the respondents.